THE INFLUENCE OF INSPIRATORY MUSCLE TRAINING ON INDICATORS OF THERAPEUTIC ALLIANCE DURING PHYSICAL THERAPY PROGRAM OF CARDIOSURGERY PATIENTS - Vitomskyi , Volodymyr (The Ukrainian Scientific Medical Youth Journal, 2021)
he aim of the work was to evaluate the impact of the inclusion of inspiratory muscle training on the formation of a therapeutic alliance within the inpatient physical therapy program after cardiac surgery. The survey involved 88 patients who underwent cardiac surgery with sternotomy and artificial circulation. Patients were randomly assigned in a 1: 1 ratio to the control group (CG, n=44) and the inspiratory muscle training group (IMТ, n=44). All patients before the operation were briefly consulted by a physical therapist about the goals and content of the physical therapy program, the algorithm of activation after surgery. The postoperative protocol of physical therapy provided for early mobilization, therapeutic gymnastics. After the operation, respiratory physical therapy in CG was limited to cough, and in the IMТ group, the Respironics Threshold IMT breathing exerciser was additionally used and, accordingly, patients were educated on the peculiarities of its use. Thus, IMТ patients were characterized by additional formation and achievement of specific goals and objectives when working with breathing exerciser, additional cooperation of the patient with a physical therapist, which was implemented in the form of explanations of the features and algorithm, control of practical implementation of breathing exercises, timely correction of errors to improve technique, motivation and diligence of the patient when performing breathing exercises with exerciser. In order to assess the level of formation of the therapeutic alliance, Working Alliance Inventory questionnaire was used. The comparison of the results of the groups by questionnaire items did not establish significant differences between the samples in any of the questionnaire items. Comparison of the results of the domains also did not establish significant differences between groups of patients. The results of the domain "goal items " were 18 (15; 19.75) points in CG and 19 (15.25; 20) points in IMТ (p = 0.259). In the "task items " domain, the CG statistics were 17 (14; 18) points, and in the IMТ 16.5 (14; 19) points (p = 0.680). Comparison of the indicators of the domain "bond items" did not establish the advantages of any of the samples: CG 16 (13,25; 18) points, and IMТ - 17 (13,25; 18) points (p = 0,681). The overall score in the groups also did not differ in CG and IMТ: 51 (43.25; 54.75) points against 52 (42.25; 56) points (p = 0.437). The additional definition, coordination and process of achieving specific goals and objectives for working with respiratory simulators did not improve the results of the therapeutic alliance, despite the fact that exercises with respiratory simulators were additional cooperation between physical therapists and patients in the inspiratory muscle training group.